Mexican cinema in times of agreements and international treaties: crisis, transformations and continuities - Hinojosa Córdova, Lucila (2016)
In this article an analysis of the reorganization appears that has had the Mexican cinematographic industry in its commercial productive circuit (production, exhibition, consumption) from the effects of the neoliberal economic policies, regulatory changes of the sector and privatizations that were implemented in the sector, as a result of the take efect of the Free Trade Agreement of North America (TLCAN or NAFTA) in 1994. The study approaches from the perspective of the political economy of the communication and the culture; is a longitudinal and descriptive study that includes the period from 1992 to 2015, in which are used like method the techniques of documentary investigation, the analysis of content and the interview.